Review: The two faces of IRE1 and their role in protecting plants from stress. (February 2021) - Li, Zhaoxia; Howell, Stephen H.
Highlights: The lumenal domain of IRE1 senses misfolded proteins in the ER lumen which activates ribonuclease activities in IRE1′s cytosolic domain. Activated IRE1 splices bZIP60 messenger RNA and attacks other messenger RNAs associated with ribosomes on the ER. The amino acid sequence of IRE1′s lumenal domain is not highly conserved among plant species, but the protein structure is conserved. The lumenal domain of IRE1 in most plant species is predicted to form near perfect beta propellers with surfaces for protein-protein interaction. IRE1 undergoes oligomerization upon activation. Abstract: IRE1 is a key factor in the Unfolded Protein Response (UPR) in plants. IRE1 is a single-pass transmembrane protein that has a lumenal domain (LD) and cytoplasmic domain (CD), which perform quite different tasks on different sides of the ER membrane. The LD recognizes the presence of misfolded proteins in the ER lumen. The LDs of IRE1 in different plant species are predicted to fold into β-propeller structures with surfaces for protein-protein interactions. Likewise, the CDs of plant IRE1s have predicted structural interfaces that promote the face-to-face arrangements of IRE1 for transphosphorylation and back-to-back arrangements for RNA splicing. Hence, the structures on the different faces of plant IRE1s have unique features for recognizing problems of protein folding in the ER and transducing that signal to activate the UPR.